2020
DOI: 10.1186/s12889-020-08509-8
|View full text |Cite
|
Sign up to set email alerts
|

Subjective social status is an important determinant of perceived stress among adolescents: a cross-sectional study

Abstract: Background: Stress is an increasing public health problem, and the association between stress and subjective social status (SSS) among adolescents has received little attention. SSS in society have shown to be associated with perceived stress, but the association between SSS in school and stress has never been examined. The aim of this study was to explore the association between SSS and perceived stress in Danish adolescent boys and girls.Methods: Data was collected in 2017 in frame of The Danish Occupation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In our sample (combined N = 58), SES is not related to age ( p = 0.737), gender ( p = 0.680), or race ( p = 0.200). Perceived Stress Scale (Cohen, Kamarck, & Mermelstein, 1984) was administered in Study 2 because it has been shown to be related to SES (Steen et al, 2020). Indeed, in our sample, lower SES is associated with greater perceived stress ( r = −0.36, p = 0.012).…”
Section: Methodsmentioning
confidence: 99%
“…In our sample (combined N = 58), SES is not related to age ( p = 0.737), gender ( p = 0.680), or race ( p = 0.200). Perceived Stress Scale (Cohen, Kamarck, & Mermelstein, 1984) was administered in Study 2 because it has been shown to be related to SES (Steen et al, 2020). Indeed, in our sample, lower SES is associated with greater perceived stress ( r = −0.36, p = 0.012).…”
Section: Methodsmentioning
confidence: 99%
“… 31 , 32 In adolescents, SSS was demonstrated to have a strong negative association with perceived stress. 33 In addition, SSS is not only associated with stress but also with factors related to increased risk of using substances to self-manage pain, such as greater negative effect and utilization of fewer active coping strategies. 34 , 35 While the literature on SSS in the college student population is limited, previous research suggests that higher levels of SSS are associated with higher levels of alcohol consumption and a greater likelihood of regular alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial stress is a significant public health concern [ 1 , 2 , 3 ] with substantial consequences, such as burnout [ 4 ], anxiety [ 5 ], depression [ 6 ], and suicide [ 7 ]. Stressed people also have more cardiovascular diseases [ 8 ], eating disorders [ 9 ], and are more overweighted or obese [ 10 ].…”
Section: Introductionmentioning
confidence: 99%